Leisure-Time Physical Activity and Physical Fitness of Male Adolescents in Oman - Khoo, Selina; Al-Shamli, A.K. (SAGE Publications, 2012)
This study investigated the relationship between leisure-time physical activity and physical fitness (cardiovascular fitness, body fat percentage, flexibility, muscle strength, and endurance) of 10th-grade male students in Oman. Data were collected from 330 students. All participants completed a descriptive questionnaire, a 1 mile walk/run test; a skinfold analysis of the chest, abdomen, and thigh; a sit and reach test; a hand grip test; and a 1-minute sit-up test. Students spent an average of 19.20 ± 6.77 hours on sedentary activities, 3.46 ± 2.11 hours on sports activities, and 11.22 ± 9.24 hours working per week. The students had an average body fat percentage of 6.38% ± 4.67%, muscle strength 38.04 ± 7.55 kg, flexibility 38.01 ± 7.41 cm, abdominal muscle endurance 38.85 ± 8.15 times/min, and cardiovascular endurance 8.10 ± 1.65 minutes.